Profile of Flexible Fiberoptic Laryngoscopy Examination Before and During the COVID-19 Pandemic in the ORL-HNS Outpatient Unit of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia in 2018–2021 - Salsabila, Aisyah Nur; Perdana, Rizka Fathoni; Awalia, Awalia; Purnami, Nyilo (Universitas Airlangga, 2025)
Highlights: No differences were observed in any of the variables before and during the COVID-19 pandemic. Only diagnosis variables differed between before and during the COVID-19 pandemic. Abstract Introduction: Flexible fiberoptic laryngoscopy (FOL) is indicated for various conditions in patients with abnormal upper airway anatomy. This study aimed to determine the profile of flexible FOL examinations at the Otorhinolaryngology-Head and Neck Surgery (ORL-HNS) outpatient unit of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from 2018 to 2021. Methods: This retrospective study used secondary data from medical records of patients who underwent flexible FOL examinations at the ORL-HNS outpatient unit from 2018 to 2021. The inclusion criteria consisted of patients’ medical records who had complete profiles, successful laryngoscopy, and diagnoses that met the specified variable criteria. Results: A total of 723 patients underwent flexible FOL at the ORL-HNS outpatient clinic during the study period. Before and during the coronavirus disease (COVID-19) pandemic, most of these patients were males, between 20 and 59 years old, unemployed, and lived out of town. The most common procedure before and during the COVID-19 pandemic was FOL. Laryngomalacia was the common diagnosis before the COVID-19 pandemic. Malignancy in the larynx was the common diagnosis during the COVID-19 pandemic. Conclusion: The variables age, sex, place of residence, occupation, and type of action remained consistent before and during the COVID-19 pandemic. However, the diagnosis variable had different results.